Mycobacterium tuberculosis cell-wall and antimicrobial peptides: a mission impossible? - Jacobo-Delgado, Yolanda M.; Rodríguez-Carlos, Adrian; Serrano, Carmen J.; Rivas-Santiago, Bruno (Frontiers in Immunology, 2023)
Mycobacterium tuberculosis (Mtb) is one of the most important infectious agents worldwide and causes more than 1.5 million deaths annually. To make matters worse, the drug resistance among Mtb strains has risen substantially in the last few decades. Nowadays, it is not uncommon to find patients infected with Mtb strains that are virtually resistant to all antibiotics, which has led to the urgent search for new molecules and therapies. Over previous decades, several studies have demonstrated the efficiency of antimicrobial peptides to eliminate even multidrug-resistant bacteria, making them outstanding candidates to counterattack this growing health problem. Nevertheless, the complexity of the Mtb cell wall makes us wonder whether antimicrobial peptides can effectively kill this persistent Mycobacterium. In the present review, we explore the complexity of the Mtb cell wall and analyze the effectiveness of antimicrobial peptides to eliminate it.